Secukinumab in psoriasis: A single-center experience - Esra Ağaoğlu; Hilal Kaya Erdoğan; Ersoy Acer; Zeynep Nurhan Saraçoğlu; Muzaffer Bilgin (Galenos Publishing House, 2021)
Background and Design: Several randomized clinical trials demonstrated the safety and efficacy of secukinumab in the systemic treatment of moderate-severe psoriasis; however, real-life data is limited. Thus, this study aimed to assess the efficacy and safety of secukinumab in patients with psoriasis. Materials and Methods: In this study, 32 patients treated with secukinumab were retrospectively reviewed. The efficacy of secukinumab was evaluated as psoriasis area and severity index (PASI) 50, 75, and 90 response rates at 16., 24., and 36. weeks, respectively. Side effects of secukinumab treatment were recorded. Results: The mean PASI of 32 patients before treatment was 12.38±6.49, which decreased to 1.96, 1.85, and 3.01, after 16, 24, and 36 weeks, respectively. At 16 weeks of treatment, 83.3% of patients reached PASI 50, 70.0% had PASI 75, and 50.0% had PASI 90 response rates. At 16, 24, and 36 weeks, PASI 50, 75, and 90 responses were generally higher in patients naive to biologic than the non-naive; however, differences were not statistically significant (p>0.05). Secukinumab was discontinued in 7 (21.9%) patients during the treatment. Of the 7 patients, 5 (15.6%) patients failed to respond to secukinumab and 2 (6.2%) developed various side effects. Oral candidiasis was observed in 4 (12.5%) patients, which was the most common side effect of secukinumab treatment. Conclusion: Secukinumab is an effective and safe treatment option in patients with psoriasis. The secukinumab efficacy in clinical practice is higher in patients naive to biologic.